Unbiased biocatalytic solar-to-chemical conversion by FeOOH/BiVO4/perovskite tandem structure - Yang Woo Lee (Nature Portfolio, 2018)
Photoelectrochemical (PEC) cell platforms typically need an electrical bias that drives the electron transfer from the photoanode to the photocathode. Here, the authors report a bias-free PEC tandem device for solar-driven redox biocatalysis.